(untitled) (Journal of Engineering, 2018)
In this paper the variable structure control theory is utilized to derive a discontinuous controller to the magnetic levitation system. The magnetic levitation system model is considered uncertain, which subjected to the uncertainty in system parameters, also it is open-loop unstable and strongly nonlinear. The proposed variable structure control to magnetic levitation system is proved, and the area of attraction is determined. Additionally, the chattering, which induced due to the discontinuity in control law, is attenuated by using a non-smooth approximate. With this approximation the resulted controller is a continuous variable structure controller with a determined steady state error according to the selected control parameters. Finally the ability and the effectiveness of the proposed continuous variable structure controller to the magnetic levitation system are verified via numerical simulations. When state initiated inside the area of attraction, the results show that the ball position can be directed to follow various desired positions, with steady state error not exceeding .